Adjusting to the euro - Gabriel Fagan; Vítor Gaspar (European Central Bank (ECB), 2007)
In this paper we argue that, for a group of converging economies of the European Union, participation in the euro area has been associated with easier access to financing by domestic economic agents. Easier access to financing was a significant impulse leading to a sharp increase in households' expenditures and a corresponding fall in the savings ratio. Increased expenditure was associated with current account deficits, a sharp fall in the net foreign asset position and an increase in the households' indebtedness. At the same time there was a sizeable increase in the real exchange rate. In this paper, we show that it is possible to obtain all these qualitative features of adjustment using a simple analytical model of intertemporal equilibrium. Specifically, we consider a simple endowment economy with traded and non-traded goods populated by Blanchard-Yaari households. We also argue that the consideration of external habit formation improves the model's ability to mimic short to medium term adjustment dynamics while, at the same time, improving the plausibility of steady state effects.
Keywords: F36; E21; F32; 330; euro area; interest rate convergence; overlapping generations model; Eurozone; Wirtschaftliche Konvergenz; Zinsstruktur; Verbraucherkredit; Sparen; Overlapping Generations; EU-Staaten